ANALYSIS OF THE USE OF AL-USLUB AL-HAKIM AND AL-SALB WA AL-IJAB IN SURAH AL-IMRAN - Muti Husnul Khotimah; Nina Wandana; Nurul Huda Hasibuan; Harun Al Rasyid (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
Uslub Al-Hakim and Thibaq al-Salab wa al-Ijab are one aspect of the study of badi' science, which is the discipline of balaghah which discusses the beauty of language style in terms of muhassinat ma'nawiyah or the beauty of meaning. This research aims to analyze the use of uslub al-hakim and thibaq al-salb wa al-ijab. This research uses library research (Library Research) with a qualitative approach method. The data sources used are library sources in the form of the Al-Qur'an, books and journals. Data collection techniques use documentation techniques. Data analysis, namely reduction, data presentation, verification and conclusions. In surah Ali-Imran, there are 7 verses containing uslub al-hakim which are classified into four forms, namely the question and answer form found in verses 37, 40, 47, 154. The form of the statement whose meaning is changed is found in verses 168, 173 and 183. The form of questions answered by questions and statements answered by questions is not found in Surah Ali-Imran. There are 27 verses that contain thibaq al-salb wa al-ijab, of which 7 verses have the meaning of thibaq al-salb including verses 66, 69, 75, 78, 86, 119 and 135. Meaning that thibaq al-ijab has 20 verses including verses 5, 8, 22, 28, 29, 29, 36, 41, 46, 83, 90, 93, 100, 103, 106, 149, 159, 160, 179 and 191. This research provides a valuable contribution to understanding the richness and complexity of the Al-Qu'an, discussing uslub al-hakim and thibaq al-salb wa al -ijab is part of the beauty of the Arabic language. This research opens up a wider space for discussion in the fields of linguistics, Arabic literature and the Islamic faith.